Contemporary Geopolitical Evolution: Theoretical Ambiguities and the Uncertain State of Multipolaritу - Gungaa, Bazarvaani (Mongolian Journal of Strategic Studies, 2025)
This article examines contemporary geopolitical transformations, the evolving structure of international power, and patterns of strategic competition through an integrated analysis of theoretical frameworks and empirical developments. In the 21st century, trilateral relations among the United States, China, and Russia have emerged as a central axis of global politics, with great power com- petition exerting substantial influence on international stability and regional security dynamics. Drawing on realist and liberal perspectives, the study analyzes the characteristics of an increasingly multipolar international system and argues that ongoing geopolitical processes challenge the explanatory boundaries of established international relations theories, generating growing theoretical ambiguity. The article introduces the concept of “multidimensional geopolitics” to capture the expansion of strategic competition into economic, technological, infrastructural, and informational domains, where power is exercised in non-military and hybrid forms. It further highlights the narrowing strategic maneuvering space available to small and medium-sized states, underscoring the necessity of adaptive strategic decision-making and interest balancing under conditions of structural uncertainty. Overall, the article contributes to scholarly debates on theoretical ambiguity, great power competition, and emerging risks to the contemporary international order. Орчин үеийн геополитикийн хувьсал: Онолын төөрөгдөл, олон төвт тодорхойгүй төлөв байдал Хураангуй: Энэхүү өгүүлэлд орчин үеийн геополитикийн өөрчлөлт, хүчний төвүүдийн стратегийн өрсөлдөөнийг онолын үзэл баримтлал болон бодит нөхцөл байдлын уялдаа холбоонд тулгуурлаж шинжилсэн болно. АНУ, БНХАУ, ОХУ-ын гурвалсан харилцаа XXI зуунд дэлхийн гол тэнхлэг болж, их гүрнүүдийн өрсөлдөөн даяарын1 тогтвортой байдал болон бүс нутгийн аюулгүй байдалд хүчтэй нөлөө үзүүлж байна. Судалгаанд реализм, либерализмын онолын хандлага, олон төвт тогтолцооны онцлогийг авч үзэхийн зэрэгцээ эдийн засаг, технологи, дэд бүтэц, мэдээллийн орон зайг хамарсан “олон хэмжигдэхүүнт геополитик” хэмээх үзэгдлийг онцоллоо. Мөн жижиг, дунд улсад оновчтой маневр хийх боломж хумигдаж буйг тэмдэглэж, стратегийн шийдвэр гаргалт болон ашиг сонирхлын тэнцвэрийг хадгалах шаардлагыг тодотгов. Энэхүү өгүүлэл орчин үеийн геополитикийн орчин онолын төөрөгдөл үүсгэж, улмаар стратегийн өрсөлдөөнийг гааруулж, олон улсын дэг журмыг өөрчилж буй явцыг ойлгоход хувь нэмэр үзүүлнэ. Түлхүүр үг: Геополитикийн хувьсал, онолын төөрөгдөл, хүчний гурвалжин, геополитикийн хэрэгсэл, орчин үеийн олон улсын харилцаа.